Schizophrenia and quality of life: a one-year follow-up in four EU countries - Xavier, Fernando Miguel Teixeira (2006)
Background: This article systematically monitors the quality of life (QOL) of patients with schizophrenia from seven different sites across four European countries: France, Ireland, Portugal and Spain. Methods: A one-year prospective cohort study was carried out. Inclusion criteria for patients were: a clinical lifetime diagnosis of schizophrenia according to ICD-10 (F20) diagnostic criteria for research, age between 18 and 65 years and at least one contact with mental health services in 1993. Data concerning QOL were recorded in seven sites from four countries: France, Portugal, Ireland and Spain, and were obtained using the Baker and Intagliata scale. At baseline, 339 patients answered the QOL questionnaire. At one-year follow-up, Spain could not participate, so only 263 patients were contacted and 219 agreed to take part. QOL was compared across centres by areas and according to a global index. QOL was correlated with presence of clinical and social problems, needs for care and interventions provided during the one-year follow-up. Results: We did not find any link between gender and QOL. There were some significant differences between centres concerning many items. What is more, these differences were relative: in Lisbon where the lowest level of satisfaction was recorded, people were satisfied with food but highly dissatisfied with finances, whereas in St Etienne, where the highest level of satisfaction was recorded, people were less satisfied with food when they were more satisfied with finances. The evolution in one year among those respondents who took part in the follow-up (excluding the subjects from Granada) showed different patterns depending on the items. Conclusion: The four countries have different resources and patients live in rather different conditions. However, the main differences as far as their QOL is concerned very much depend on extra-psychiatric variables, principally marital status and income.